Plants can't sit still - Hirsch, Rebecca E. (Millbrook Press, 2016)
Describes some ways in which plants can move, from sunflowers turning towards sunlight and vines creeping up a fence to tulips folding in at night and maple seeds whirling like helicopters in the wind.